Optical Measurement of Stem Xylem Vulnerability. Issue 4 (6th July 2017) - Brodribb, Timothy J.; Carriqui, Marc; Delzon, Sylvain; Lucani, Christopher
Abstract : An optical method is shown to accurately measure the vulnerability of stem xylem to cavitation during water stress. Abstract: The vulnerability of plant water transport tissues to a loss of function by cavitation during water stress is a key indicator of the survival capabilities of plant species during drought. Quantifying this important metric has been greatly advanced by noninvasive techniques that allow embolisms to be viewed directly in the vascular system. Here, we present a new method for evaluating the spatial and temporal propagation of embolizing bubbles in the stem xylem during imposed water stress. We demonstrate how the optical method, used previously in leaves, can be adapted to measure the xylem vulnerability of stems. Validation of the technique is carried out by measuring the xylem vulnerability of 13 conifers and two short-vesseled angiosperms and comparing the results with measurements made using the cavitron centrifuge method. Very close agreement between the two methods confirms the reliability of the new optical technique and opens the way to simple, efficient, and reliable assessment of stem vulnerability using standard flatbed scanners, cameras, or microscopes.